Investigation Of The EMG-Angle Relationship In The Upper-Limb Muscles During Isometric Contraction - Sundaraj, Kenneth; Rabbi, Mohammad Fazle; Ahamed, Nizam Uddin; Alqahtani, Mahdi; Altwijri, Omar; Ghazali , Kamarul Hawari (Scientific Publishers of India, 2017)
The relationship between EMG and elbow angle was investigated to identify the signal characteristics of upper-limb muscles during isometric contraction.The study would improve the current understanding of electrophysiological activities of the human upper limbs, which would aid the development of prosthetic arms for rehabilitation research.Subjects and methods:Ten subjects aged 22.4(±1.5) years participated in this study.The electromyography signals from the biceps brachii muscle were recorded during isometric contraction.The root mean square and mean absolute value of the EMG signals were calculated and evaluated to assess the relationship between the signals and elbow angles.In addition,the force exerted by the upper limb was recorded using a dynamometer to identify more features of the relationship.Results:The results revealed that both the RMS and MAV of the EMG signals are not significantly related with the elbow angle (r2=0.70 and 0.21;p=0.075 and 0.43, respectively).In contrast,the force is strongly related to the elbow angle (r2=0.88,p=0.017).Conclusion: A stronger electrical signal was generated by the upper-limb muscles with an increase in the angle of the elbow joint,whereas a lower force was obtained with an increase in the elbow joint angle.